Answer:
Option B. 7 is the correct answer.
Explanation:
The given expression is
![\sum_(t=1)^(3)[{4* ((1)/(2))^(t-1)}]](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ykgczu40fyrkp82dogjzhzkumxfwvr8re6.png)
Now by putting the the values of t = 1, 2, 3 we get the sequence.
Then we can add the terms of the sequence
First term =
![4.((1)/(2))^(1-1) = 4.1 = 4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/hrm7jiv06exnkayjwrcdurptqdm6aibem6.png)
Second term =
![4.((1)/(2))^(2-1)=4.((1)/(2)) = 2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/9g61wqjzwg82wbgon8ivnh5o2obxjjq4w8.png)
Third term =
![4.((1)/(2))^(3-1)=4.((1)/(2))^(2)=4.(1)/(4)=1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8tvn4lxns0v14leucd9zk37zbhh08617hp.png)
So the total of these terms will be = 4 + 2 + 1 = 7
Answer is 7.